United States Marine Corps Performance Pricing Model - Kelly, Patrick J. (Monterey, California: Naval Postgraduate School, 2012)
Approved for public release, distribution unlimited === Logistics, Headquarters Marine Corps, located at the Navy Annex in Washington D.C., has requested this study to develop pricing models for Operating/Crew, Field levels, and Sustainment level of maintenance in order to predict maintenance funding requirements at the Marine Forces (MARFOR) level. The inputs will include historical inventory quantities for MARFOR equipment and corresponding cost data for each echelon of maintenance.